A Robust Adaptive Nonlinear Control Design via Geometric Approach for a Quadrotor. Issue 6 (2nd November 2022) - Guendouzi, Awatif; Hamerlain, Mustapha; Saadia, Nadia
Abstract : This paper addresses the design of an adaptive sliding mode controller via geometric approach for a quadrotor unmanned aerial vehicle (UAV), suffering from inertial parameter uncertainty and disturbances. For this aim, the quadrotor dynamics described on the special Euclidean group SE(3) is decomposed into two cascaded subsystems, where the backstepping controller is developed during the position subsystem to obtain the necessary thrust magnitude and the reference orientation for the attitude subsystem. Then we develop a robust controller for the attitude subsystem via an exponential reaching law using the gain adaptation approach which has the advantage of robustness to bounded uncertainties/perturbations with unknown bounds in which the exponential coordinates are employed to parameterize the rotation matrix that pertains to a natural parameterization about the neighborhood of the identity. And this neighborhood covers all of SO(3) except a zero measure set. Finally, the simulation results are given in order to show the performances and the effectiveness of the proposed method.